Increasing Employee Performance of Gideon Mula Gabe Ltd. Company by Increasing The Employee Experience of The Company (The Indonesian Journal of Business Administration, 2021)
Every company has got affected by pandemic COVID-19. But, the low performance of the company is not only because of the domino effect of the economy. Based on Deloitte Human Capital Research there is change within the habits and preference of the employees that caused by COVID-19 they more likely prefer well-beingness than any other benefits. The fact is many companies still not taking this seriously and provide low investment for the well-beingness of their employees. As a company that affected and have similar symptom within the result of Deloitte Human Capital Research, the researcher which also the CEO of Gideon Mula Gabe Ltd. company want to explore the relationship between employee experience as the tools to get well-beingness and employee performance which at the end of the day affected company performance especially within the company that running in Palm Oil Plantation Industry. Also, to find the business solution that can increasing and have stability due to uncertainty in the future and created well beingness within the company. This research taking 100 employees as the participation respondent, and using a questionnaire with the Likert Scale as the parameter to answer. The results show there is a positive relation between Employee Experience and Employee Performance. Solution found are Digital Experience, Employee Housing, and Digital Farming.Keywords: COVID-19, Employee Performance, Employee Experience.